RANCANG ULANG SISTEM PENDINGIN PADA MESIN FREEZER MULTIFUNGSI - Mukhamad Zidan N; George Endri Kusuma; Projek Priyonggo (Proceedings Conference on Marine Engineering and its Application, 2023)
Previous research was the beginning of the manufacture a multifunctional freezer, a machinethat has two functions for cooling and drying and is aimed at preserving fish both dried and cooled.The evaporator on the machine is used for cooling the fish in the refrigerator. The cooling process hasa weakness in the cooling system where the temperature in the chamber can’t reach a temperaturebelow 0°C when the load is given above 0,5kg, and its cooling rate is less efficient so that the processof temperature reduction in a chamber given the load variation has a long enough time, so it can beconcluded that the performance of the chiller is less optimal. In this final project, a cooling systemredesign is carried out on a multifunctional freezer machine, as well as a capillary tube with a diameterof 0,31 inches and a length of 1,5 meters. Test results were obtained with weight variations of 0,5kg,2kg, and 3kg. Average cooling speed of 0,255 kJ/s, chill room temperature of 2,7°C to -6°C, and thebest coefficient of performance are obtained from the test results at a weight of 3kg with a COP valueof 6,609 at 30 minutes and 5,133 at a test time of 60 minutes or 1 hour of operation of the multifunctionfreezer.